Correlation of total serum HDL particles with a predictor of mortality risk in idiopathic pulmonary fibrosis. Issue 4 (14th April 2022) - Yasuma, Taro; D'Alessandro-Gabazza, Corina N.; Fujimoto, Hajime; Kobayashi, Tetsu; Gabazza, Esteban C.
We read with great interest the article published in your journal by Barochia et al . [1]. The authors reported that the serum level of small high-density lipoprotein particles measured by nuclear magnetic resonance spectroscopy (S-HDLPNMR ) is negatively associated with death or lung transplantation in idiopathic pulmonary fibrosis (IPF) [1]. The finding is consistent with the protective activity of high-density lipoprotein (HDL) in tissue injury and fibrosis reported in previous studies [2–5]. Measurement of serum total HDL particles may be potentially useful as a biomarker in idiopathic pulmonary fibrosis https://bit.ly/3K7D3q6